Deepening Divides - Fassin, Didier (Pluto Press, 2021)
At a glance, 'borders' and 'boundaries' may seem synonymous. But in the real (geopolitical) world, they coexist as distinct, albeit overlapping entities: the former a state's delimitation of territory; the latter the social delineation of differences.